Approaching the 50th anniversary of the first Fontan procedure. What is the current state of treatment provided to patients with functional single ventricles? - Cześniewicz, Paweł; Kusa, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Nearly 50 years after the pioneering procedure performed by Francis Fontan and Eugene Baudet, which has saved the lives of thousands of children, there are still more questions than answers regarding therapeutic management. The complex pathophysiology of Fontan circulation, the lack of clear guidelines, and the shift in the care of such patients from pediatric cardiological and cardiac surgical centers to ones dealing with adult patients, cause new threats. This paper outlines the fundamental issues related to the pathophysiology of Fontan circulation and reviews the literature on the methods of treating complications characteristic of this group of patients.